2021
DOI: 10.1101/2021.04.24.440790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A divergent protein kinase A in the human pathogenLeishmaniais associated with cell cortex microtubules and controls cell shape

Abstract: Parasitic protozoa of the genus Leishmania cause human leishmaniasis. They cycle between the phagolysosome of mammalian macrophages, where they reside as round intracellular amastigotes, and the mid-gut of female sand flies, which they colonize as elongated extracellular promastigotes. Shifting promastigotes to a lysosome-like environment (pH 5.5 and 37°C, 5% CO2) initiates their development into amastigotes. Previous studies suggested a role for protein kinase A (PKA) in this differentiation process. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Here, we used a genetic approach combined with fluorescence- and video-microscopy, to dissect the localisations and paring preferences of the three L. mexicana PKAC and two PKAR proteins and studied how gene deletions impacted cell swimming and generation of flagellar waveforms. Our results corroborate recent reports of PKAC/R pairings in Leishmania (55) and extend previous analyses on PKA function by providing multiple lines of evidence for a vital function for Lmx PKAC1 in flagellar beat regulation. We found that there are two regions of PKA concentration in promastigote forms: Lmx PKAC1, Lmx PKAC2 and Lmx PKAR1 showed enrichment in the flagellum, while a strong cell body cortex signal was detected for Lmx PKAC3 and Lmx PKAR3.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we used a genetic approach combined with fluorescence- and video-microscopy, to dissect the localisations and paring preferences of the three L. mexicana PKAC and two PKAR proteins and studied how gene deletions impacted cell swimming and generation of flagellar waveforms. Our results corroborate recent reports of PKAC/R pairings in Leishmania (55) and extend previous analyses on PKA function by providing multiple lines of evidence for a vital function for Lmx PKAC1 in flagellar beat regulation. We found that there are two regions of PKA concentration in promastigote forms: Lmx PKAC1, Lmx PKAC2 and Lmx PKAR1 showed enrichment in the flagellum, while a strong cell body cortex signal was detected for Lmx PKAC3 and Lmx PKAR3.…”
Section: Discussionsupporting
confidence: 92%
“…Several reports have highlighted the existence of a second PKAR-like protein within the trypanosomatids (53,54), which was recently given the name PKAR3 in L. donovani (55); for consistency, we adopt this terminology here . L. mexicana has a syntenic orthologue of PKAR3 (Table 1) (Supplementary Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to R1, Leishmania genome encodes LdPKAR3 (LinJ.34.2680) that similar to R1 form heterodimers with LdPKAC subunits and is cAMP-independent. In LdPKAR3, the C-terminus half is conserved with higher Eukaryotes while the N-terminus half is divergent and most likely unstructured (Fischer-Weinberger et al, 2021).…”
Section: Protein Kinase a Is The Differentiation Gatekeepermentioning
confidence: 99%
“…Recent experiments indicate that LdPKAR3 is covalently bound to the subpellicular microtubules at the cell cortex. R3 associates with C3, and this association is important for the elongated shape of promastigotes (Fischer-Weinberger et al, 2021).…”
Section: Protein Kinase a Is The Differentiation Gatekeepermentioning
confidence: 99%